Pengaruh Audit Tenure dan Audit Market Concentration Terhadap Kualitas Audit Syariah - Rindy Anticha; Usdeldi Usdeldi; Ferri Saputra Tanjung (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of audit tenure and audit market concentration on sharia audit quality in companies included in the Jakarta Islamic Index (JII) and listed on the Indonesia Stock Exchange for the 2019–2023 period. This study uses a quantitative approach involving 20 companies in the Jakarta Islamic Index (JII) and listed on the Indonesia Stock Exchange for the 2019-2023 period, resulting in 100 data. This study uses secondary data collection through the company’s annual report. The analysis method in this study uses logistic regression analysis and statistical testing through the Wald test and simultaneous test (Omnibus Test). The results of the study indicate that partially, audit tenure has a negative and significant effect on sharia audit quality, indicating that the length of the relationship between the auditor and the client can reduce auditor independence. Conversely, audit market concentration has a positive and significant effect on sharia audit quality, indicating that market dominance by large auditors can increase audit professionalism and accuracy. Simultaneously, both variables are proven to have a significant effect on the quality of sharia audits, although the coefficient of determination (Nagelkerke R Square) of 0.291 indicates that there are still other variables outside the model that contribute 70.9%. This finding provides important implications for Public Accounting Firms, sharia companies, and further researchers in efforts to improve the quality and integrity of sharia audits in Indonesia.